Segmenting tourism in rural area by emphasizing on motivational factors: Case study of Kolan river catchment area - Nasser Bayat; Seyed Ali Badri (تحقیقات کاربردی علوم جغرافیایی)
This research is conducted on tourist segmentation in the touristy catchment area of Kolan river in Malayer Township. The statistical population is tourists who travel to the area for recreation, tourism and leisure. The research tool is a self-administrated questionnaire. By the method of Simple random sampling we collected a total of 200 questionnaires of tourists in the study area. Descriptive statistics and exploratory factor analysis and cluster analysis was used to analyze the research data. Based on the results of factor analysis were identified even major factor in tourists' motivations at the regional level, including: Rurality, sense of place and place belonging, rest and relaxation, nature-based tourist activities, group outdoor recreational activities, purchase the rural production, excitement and novelty, spirituality and solitude. According to this motivational factors final result of tourism segmentation shows that tourism demand in the market consisted 7 difference segments. cluster 1 with a diverse motivation of 12%, cluster 2 with togetherness motivation 17%, third cluster as a younger age group with adventure motivation 18.5%, cluster 4 with rurality motivation 15%, fifth cluster whit shopping motivation 10%, sixth cluster with sense of place and desire for comfort and rest 19.5%, and seventh cluster with a particular tendency to sense of place 7.5% of the sample population as a whole. The results could be utilize in order to optimize the use of available resources in the area by managers and local authorities, as well as owners of tourism businesses, compatible with the actual needs of  various sectors in rural tourism market.